Development of a Risk Analysis Application for Higher Education Institutions Using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) Methodology - Putra, Rizaldi; Sanjaya, Memet; Adelia, Kinanti Dwi; Fathimah, Neng Siti (JISA(Jurnal Informatika dan Sains), 2025)
In general, higher education institutions in Indonesia continue to face challenges in accurately mapping risks identified through Internal Quality Audits (IQA), resulting in limited collective management awareness of risk-based operations. Specifically, this study highlights that similar conditions persist in Cikarang, West Java, where risk identification and control processes remain insufficiently integrated into institutional quality improvement strategies. Although routine audit findings are successfully collected, the subsequent follow-up process is often unstructured and fails to prioritize the most crucial improvements. This research addresses these challenges by developing an application. Digital system adapted from the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methodology. That enables managers to collaboratively determine the risk level associated with each finding. The system also facilitates the categorization of findings based on the urgency of required corrective actions and prioritization for subsequent mitigation efforts. This application is designed to facilitate the conversion of every evaluation finding into a measurable risk score. The primary objective of this system is to deliver comprehensive visualization and mapping of risks through a collaborative process, enabling groups to identify the impact of each finding, conduct analysis and discussion to determine probability, exposure, and consequence, and classify the results into categories of very high risk, high risk, substantial risk, moderate risk, or low risk.